Involvement of DAO to Cd-stress in cucumber seedlings - Janicka, Małgorzata (2021)
Cucumber (Cucumis sativus L.) is a crop plant, the third most-produced vegetable and is being developed as a new model plant. In recent years, heavy metals pollution has become a more serious global problem, that affect crop production. An anthropogenic and industrial activities have led to high emission of Cd into the environment. Plants have applied several adaptive strategies to diminish the toxic effects of Cd. They can remove excess toxic ions of heavy metals from the cytoplasm to the outside of cells using the heavy metal/proton antiport. The proton gradient needed for the action of the antiporter in the plasma membrane (PM) is generated by the PM proton pump (PM H+-ATPase). Plants also adapt to Cd toxicity by activating signaling pathways that allow them to function (grow and develop) under conditions of cadmium stress. ROS-signaling is very important here. There are many potential sources of hydrogen peroxide production in plant cells. One of them is the degradation of polyamines (PAs), which contributes to an increase in extracellular H2O2 level. PAs play a crucial role in the responses of plants to abiotic stresses. They are oxidatively deaminated by amine oxidases including flavin adenine dinucleotide (FAD) dependent polyamine oxidases (PAO) and copper amine oxidases (CuAO) also called diamine oxidases (DAO). In this study it was observed that treatment of plants with Cd stimulated the diamine oxidase (DAO) activity twice. In our earlier study we have shown that under cadmium stress the PM H+-ATPase activity increased in cucumber seedlings roots. Now it was shown, that the stimulating effect of Cd on the PM H+-ATPase activity and expression of 3 genes encoding proton pump (CsHA2, CsHA4, CsHA8) was reduced by aminoguanidine (AG, DAO inhibitor). Moreover we have observed, that H2O2 produced by DAO, promotes the formation of NO in the roots of cucumber seedlings. NO and H2O2 are important signaling molecules in plant responses to abiotic stresses by modification of PM H+-ATPase activity. Results presented in this work showed that DAO could be an important element in the signal transduction pathway leading to an increase in PM H+-ATPase activity under cadmium stress This results provide new insight into polyamines mediated signaling and H2O2 and NO as a potential mediator of PA actions under cadmium stress.
Keywords: NO; H2O2